Pengaruh Konflik Pekerjaan-Keluarga Pada Kepuasan Kerja Berdasarkan Jenis Kelamin ( Studi Pada Guru di Kota Yogyakarta) - , ANRIKHAN NOOR FIRDAUS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study was to examine whether or not there are different levels of job satisfaction between men and women, the level of work-family conflict among different between men and women as well as to test the effect of work-family conflict were different between men and women on job satisfaction. The results of this study showed no difference in levels of satisfaction between male teachers and female teachers, there is no difference in the level of family work conflict between male teachers and female teachers. And there is no difference in the effect of work-family conflict were significant between male teachers and female teachers on job satisfaction. The school can reduce work-family conflict perceived teacher by organizing a family day at the weekend, for example, held a joint tourist families into an area, work out together at the weekend, set the working hours of teachers in a way when teachers have additional duties such as checking task of students that should be completed during working hours and not brought home and hold counseling sessions for teachers, so that teachers can spend complaint regarding family issues.